Hakikat Agama dan Esensi Beragama Dalam Islam: Studi Qur’an dan Hadits. - Mauzifa (Penerbit Hellow Pustaka, 2026)
The essence of religion needs to be studied deeply and rationally in the context of Islam. The author examines through the Qur'anic literature, Hadith, and sources relevant to the context of the theme of the discussion, analyzes, and compiles the results in this article. This study shows that human beings are naturally religious, and Islam is a religion that is pleasing to Allah, becoming a guideline for life that guarantees survival in this world and the hereafter. The Qur'an is the main guideline in Islam. Religion plays a role in maintaining human life as a whole, both material and spiritual, and being the moral controller of individuals. Psychologically, religion improves well-being and shapes personality through ethics, spirituality, and social norms. In the sociological aspect, religion regulates social harmony and prevents conflict. Religion also forms morality as a guide to behave and achieve the good of the hereafter. Islam as a religion that is pleasing to Allah requires Muslims to live a life according to the Qur'an and hadith to achieve happiness in the diversity of their practices. There are five dimensions in the aspect of religion, namely belief, practice, experience, knowledge and practice